PENGEMBANGAN MEDIA PEMBELAJARAN NETADO UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DAN MEMBACA DONGENG SISWA KELAS II SDN BANGSONGAN - Prisna Galuh Ardhia Pramesti; Alfi Laila; Erwin Putera Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of learning media at Bangsongan Elementary School is less varied and learning outcomes are still low based on the results of observations and distribution of teacher questionnaires and tests for students. This research aims to 1) determine the validity 2) practicality and 3) effectiveness of netado media. The method used is the R&D (Research and Development) method with the ADDIE development model. Data collected through media and material validation questionnaires, teacher and student response questionnaires, as well as pretest and posttest for pre-requisite tests 1) normality test, 2) homogeneity test, and 3) T test. Through media and material expert validation results, percentages were obtained 87.5% and 90% which can be said by the media are valid. Furthermore, when administering the teacher and student response questionnaire, a percentage score of 92% and 95% was obtained, which stated that the media was practical to use. In the normality test, it is known that the results are 0.287 > 0.05, limited test and 0.257 > 0.05, so it is said that the data used is normal. Furthermore, the homogeneity test obtained results of 0.543 > 0.05 limited test and 0.185 > 0.05 broad test, so it can be said that the data used is homogeneous or similar. Finally, the T test obtained results of 0.001 < 0.05 limited test and 0.001 < 0.05 broad test, so it can be said that there are differences in the different treatments, namely the use of netado media.